Do the use of lecithin and lysolecithin as feed emulsifiers enhance poultry production? A meta-analysis - Tri Puji Priyatno; Danung Nur Adli; Mohammad Miftakhus Sholikin (Italian Journal of Animal Science)
A meta-analysis was conducted to assess the impact of lecithin and lysolecithin as emulsifying agents on egg production, growth performance, nutrient digestibility, blood profiles, and carcase quality in poultry. The dataset was compiled from published articles between 1964 and 2024, using the Population, Intervention, Comparison, and Outcome (PICO) framework: P = poultry, I = addition of lecithin and lysolecithin, C = control vs. treatment, and O = growth and production parameters. Following quality evaluation, the final dataset comprised 40 articles, including 33 studies on broiler chickens, 2 studies on ducks, 4 studies on laying hens, and 1 study on turkeys. The overall results of the meta-analysis indicated that lecithin and lysolecithin significantly improved growth performance and digestibility (p < 0.01) in a robust model, although the effects on digestibility were not consistent across all the models. Lecithin also demonstrated a strong positive effect (p < 0.001) on reducing cholesterol in a robust model. However, there was a significant trend (p < 0.01) in the liver percentage for both ducks and turkeys, as shown in the robust model. Conversely, lecithin and lysolecithin had no significant effects on the hot carcase weight percentage, breast percentage, egg mass, egg weight, or hen-day production (HDP). In summary, lecithin and lysolecithin function effectively as emulsifying agents, particularly by enhancing growth performance rather than egg production, with varying degrees of significance.